Internalisasi Nilai-Nilai Penguatan Pendidikan Karakter Melalui Pembelajaran Tematik Muatan PKn pada Masa Pandemi COVID-19 di Kelas V - Robi Apriansyah; Puspa Djuwita; Bambang Parmadie (UNIB Press, 2022)
This study discusses the internalization of the values of strengthening character education through thematic learning of Civics content during the COVID-19 Pandemic in class V SD Negeri 32 Seluma. The purpose of this study is to describe the planning, implementation, and evaluation of Civics Thematic learning as an internalization of PPK values during the COVID-19 pandemic in class V SD Negeri 32 Seluma. The type of this research is descriptive qualitative with data sources consisting of principal, teacher, students, and parents of students. The results of the study indicate that the internalization of the values of strengthening character education has been carried out through the learning process. At the planning stage, values are integrated in lesson plans, teaching materials, and student worksheets (LKPD). At the implementation stage, values are integrated in the stages of learning and providing teaching materials. As for the evaluation stage, values are integrated in the assessment of learning outcomes, attitude assessment journals, and counseling guidance agenda books.